Prediction of excited‐state properties of oligoacene crystals using polarizable continuum model‐tuned range‐separated hybrid functional approach. Issue 9 (19th January 2017) - Hu, Zhubin; Zhou, Bin; Sun, Zhenrong; Sun, Haitao
Abstract : A methodology combining the polarizable continuum model and optimally‐tuned range‐separated (RS) hybrid functional was proposed for the quantitative characterization of the excited‐state properties in oligoacene (from anthracene to hexacene) crystals. We show that it provides lowest vertical singlet and triplet excitation energies, singlet‐triplet gap, and exciton binding energies in very good agreement with the available experimental data. We further find that it significantly outperforms its non‐tuned RS counterpart and the widely used B3LYP functional, and even many‐body perturbation theory within the GW approximation (based on a PBE starting point). Hence, this approach provides an easily applicable and computationally efficient tool to study the excited‐state properties of organic solids of complexity. © 2017 Wiley Periodicals, Inc. Abstract : Oligoacene crystals are well‐known as promising candidates for optoelectronics applications. Theoretical investigation of their excited states still remains challenging. A methodology combining the polarizable continuum model and optimally‐tuned range‐separated hybrid functional was proposed for the quantitative characterization of the lowest vertical singlet and triplet excitation energies, singlet‐triplet gap, and exciton binding energies of oligoacene crystals. The results were shown to be in very good agreement with the available experimental data.